(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article presents the factors that negatively affect the consciousness of young people in the context of globalization and recommendations for their prevention, discusses the work that needs to be done in terms of information and psychological security. Today, it is important to protect young people from various alien ideas, the negative effects of the virtual world, since this is a matter of state policy, not to weaken work in this direction, to carry out them consistently and systematically, to educate young people in patriotism, ideological immunity, and a culture of information consumption. This is one of the urgent tasks facing the wide scientific community, parents and every conscious citizen. The Internet gives children more information than teachers at school and parents at home. But, it should be borne in mind that not all information on the Internet has a positive effect on the growth of the level of intelligence. In today’s era of globalization, in these turbulent times, it would not be enough to think only about the physical health of children. Society needs not only highly educated cadres, but also spiritually rich, socially competent people who combine in themselves universal human values ??as a family, Motherland.